Comparative analysis of prebiotic effects of seaweed polysaccharides laminaran, porphyran, and ulvan using in vitro human fecal fermentation - Hyunbin Seong; Jae-Han Bae; Ji Sun Seo; Seul-Ah Kim; Tae-Jip Kim; Nam Soo Han (Journal of Functional Foods, 2019)
Laminaran, porphyran, and ulvan are major seaweed polysaccharides in brown, red, and green algae, respectively. We compared their prebiotic effects using individual microbial fermentability test and in vitro fecal fermentation. The fermentability test showed that these polysaccharides were selectively utilized by Bifidobacteria, Lactobacilli, and Bacteroides (ΔOD580 nm, 0.2–1.0), while no growth of harmful bacteria was observed. In vitro fecal fermentation for 24 h showed growth stimulation effect of laminaran on Bifidobacteria (Δ8.3%/total bacteria) and Bacteroides (Δ13.8%/total bacteria) promoting the production of acetate and propionate. Ulvan exhibited same result on Bifidobacteria (Δ8.5%/total bacteria) and Lactobacillus (Δ6.8%/total bacteria) promoting the production of lactate and acetate; however, porphyran showed little prebiotic effect. Laminaran was fermented slowly compared to fructooligosaccharides and this may permit production of short-chain fatty acids in distal colon. This in vitro study demonstrates that the seaweed polysaccharides tested, particularly laminaran and ulvan, have prebiotic effects on microbiota in human colon.